From embryo to sexual maturity: chronic BPA exposure under elevated contamination scenarios induces multi-organ toxicity in marine medaka (Oryzias melastigma) - Yangmei Li; Zhang Huan; Qin Lin; Junyi Liu; Wenyang Xiao; Ning Zhang; Zailiang Li; Yanping Zhang; Yusong Guo; Zhongduo Wang; Zhongdian Dong (Marine Pollution Bulletin, 2026)

Screening, characterization and calcium-binding properties of novel yak milk peptides - Bo Zhao; Xinyi Li; Yanping Guo; Wenting Li; Torkun Mamet; Nidhi Bansal (International Dairy Journal, 2026)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Upcycling lignocellulosic biomass using a radial-axial fixed-bed ex-situ catalytic pyrolysis reactor - Fuzheng Li; Jinping Guo; Xingshan Shi; Weiling Piao; Cristina Franch; Yanping Chen; K. Seshan; Songbo He (Bioresource Technology, 2026)

Fermentation with aspergillus costiformis enhances the anti-migratory activity of Aquilaria sinensis leaves with possible involvement of MAPK-related pathways - Lianqun Wu; Xizhi Zhu; Xinyue Wang; Yanping Wu; Qian Bu; Tonglin Dai; Xing Wen; Kai Zhong; Hongwei Guo; Hong Gao (Food Research International, 2026)

Insight into the dynamic metabolic transformations and flavor characteristics during solid-state fermentation of Huangjinya dark tea by Eurotium cristatum PW-1 - Yangyu Zhou; Jiuhong Du; Huan Guo; Yanping Wu; Kai Zhong; Yue Xiao; Yina Huang; Hong Gao (Food Research International, 2026)

Unveiling microbial sulfate reduction in Acid Mine Drainage Treatment using a Chained Environmental-Microbial machine learning approach - Yanping Deng; Beiyi Xiong; Hao Chen; Yongyang Wang; Xin Liu; Chuling Guo; Zhi Dang (Chemical Engineering Journal, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

Upcycling waste glass into chitosan-modified zeolite for heavy metal immobilization and deep mineralization: A "waste-treats-waste" paradigm - Xinxin Li; Rongxin Guo; Zhihan Zhang; Yifeng Zou; Ziyi Yang; Dexun Zou; Yanping Liu (Process Safety and Environmental Protection, 2026)

Structure-reactivity relationship of monomeric flavan-3-ols in forming ethyl-linked anthocyanin pigments: an integrated experimental and computational study - Xu Zhao; Yanping Guo; Zihao Ye; Xinke Zhang; Qichen Yuan (Food Chemistry, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

GmHMGR6 enhances salt stress tolerance in soybean through modulation of nitrogen metabolism - Xinjie Feng; Hongzhen Liu; Yingyue Zhang; Yanping Li; Zhengxing Guo; Rong Bao; Xiuli Zhang; Xinying Liu; Huihui Zhang (Plant Cell Reports, 2026)

Distribution and potential provenance of metal nanoparticles in sediment core from Daya Bay, northeastern South China Sea - Yumei Song; Dingcheng Wang; Qiaoli Zhong; Shengda Wu; Yanping Zhao; Shuchai Gan; Yulei Xie; Puoengran Guo (Journal of Hazardous Materials, 2026)

Carbon source determines microbial synergy and metabolic resilience in sulfate-reducing bacterial communities under nitrate stress - Yanping Deng; Siyu Zhang; Zhenchen Xie; Hao Chen; Meihui Ren; Changdong Ke; Chuling Guo; Zhi Dang (Journal of Environmental Chemical Engineering, 2026)

Recyclable standardized sludge for performance evaluation of low-temperature drying units: Preparation and feasibility verification - Yuting Qin; Yanping Guo; Yongyou Hu; Jingyu Liu; Guanying Huang; Guanghuan Li; Haochun Chen; Qingying Huang (Journal of Environmental Management, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Insight into the oxidation mechanism of low-salt Sichuan-style sausages treated with inclusion complexes of tea-polyphenol/β-cyclodextrin/NaCl and electron beam irradiation using machine learning algorithms - Ya Liu; Jiuhong Du; Wenyi Ran; Lihui Huang; Wenyue Yu; Huan Guo; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2026)

Mitigating intrinsic defects and optimizing interfacial energetics via aluminum-doping toward 13.6% efficiency kesterite solar cells - Xinyu Zhang; Jingyi Meng; Zhenyan He; Chun Guo; Linxin Gao; Yanping Song; Wenjie Zhu; Sisi Jia; Busen Zhai; Lunkan Shen; Dipeng Xu; Huanhuan Sun; et al. (Chemical Engineering Journal, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Fungal communities dominate accumulation of microbial necromass carbon after 11-year revegetation in a semi-arid desert mining area - Pengfei Li; Wenjiang Fu; Yiwei Bai; Daren Zhou; Shiqi Sun; Qiao Guo; Jianguo Zhang; YanPing Miao; Hangxian Lai (Journal of Environmental Management, 2026)

Exfoliation characteristics of tetrahydrofuran on surface-active structure of different coals and its inhibition effect on oxidation - Jun Guo; Yunfei Wu; Hu Wen; Yin Liu; Yongfei Jin; Changming Chen; Yanping Quan (Fuel, 2026)

Hydroxylamine enhanced Fe(Ⅱ)-activated peracetic acid process to promote short-chain fatty acid production during sludge anaerobic fermentation - Jing Zhang; Yanping Zhang; Junliang Dong; Fen Li; Zhenjie Guo; Yibing Li (Journal of Environmental Chemical Engineering, 2025)

Study on the mechanism of influence of group extraction on low-temperature spontaneous combustion characteristics of lignite - Changming Chen; Jun Guo; Hu Wen; Yin Liu; Bo Gao; Yunfei Wu; Yanping Quan (Fuel, 2025)

Superior energy storage and charge-discharge performance achieved in (Pb1-3/2La )(Hf0.9Sn0.1)O3 antiferroelectric ceramics - Shuifeng Li; Xiaobin Guo; Zhenhua Tang; Xin-gui Tang; Qijun Sun; Yanping Jiang; Wenhua Li; Qiuxiang Liu (Chemical Engineering Journal, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

Effect of different aroma types of baijiu on the quality of Sichuan paocai - Lihui Huang; Ling Li; Lianqun Wu; Huan Guo; Yanping Wu; Kai Zhong; Hong Gao (Food Chemistry, 2025)

Absorptive and transport roots of two tree species respond differently to soil salinity along soil depth - Yan Wang; Xiaohui Guo; Qiulin Bi; Wen Zhou; Hongxi Yao; Jiacun Gu; Yanping Wang (Flora, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

The latest advances on the formation, exposure level and control strategies of nitrosamines in meat, poultry and fish products - Minting Guo; Yanping Xian; Xiaojuan Zhao; Min Qian; Jun Li; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

High entropy relaxation ferroelectric ceramics with strong coupled achieved by framework structure guided design and grain boundary optimisation - Renkai Zhao; Kaijie Chen; Wenhua Li; Xingui Tang; Zhifei Jian; YongXi Liang; Jiayi Yin; Yanping Jiang; Xiaobin Guo; Kai Yan (Chemical Engineering Journal, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Development of hydroxyapatite-based Carboxymethylcellulose-Al(III) aerogel beads for efficient and selective defluorination from brick tea infusions - Wenyue Yu; Huan Guo; Ya Liu; Yangyu Zhou; Yue Xiao; Jinrong Bai; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Carbohydrate Polymers, 2025)

Monotonic simple shear characteristics of K 0 highly over-consolidated and remolded Wenzhou clay - Zheng Yu; Yanping He; Hao Wu; Lin Guo (Marine Georesources & Geotechnology, 2025)

The behavior of NOM-Cu(Ⅱ)colloids at the goethite interface - Yuekang Chen; Lijuan Zeng; Kai Chen; Meiling Yin; Xiongkai Zheng; Yuting Zhou; Yanping Deng; Jiehong Ye; Zhi Dang; Chuling Guo (Water Research, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Montmorillonite-enhanced Carboxymethylcellulose/Polyethyleneimine aerogel: A highly efficient and reusable adsorbent for caffeine removal from tea infusions - Wenyue Yu; Yangyu Zhou; Ya Liu; Huan Guo; Lihui Huang; Lu Feng; Jinrong Bai; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2025)

Extracellular metabolites relieve the inhibitory effect of ferrous ions on microbial reduction of schwertmannite - Changdong Ke; Qian Yao; Yanping Deng; Siyu Zhang; Zhiliang Li; Renren Wu; Chuling Guo; Zhi Dang (Chemical Geology, 2025)

Study on liquid phase separation phenomenon by constructing multi-physics field model - Kerong Guo; Houjun Gong; Rongpei Shi; Yuanfeng Zan; Yihui Guo; Xingjun Liu; Yanping Huang (Annals of Nuclear Energy, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Lycorine provides antiviral activities against mandarin fish ranavirus via suppressing apoptosis and activating type I interferon pathway - Mengyan Jia; Yanping Ma; Le Hao; Ziqian Tao; Jingya Wang; Sentai Liao; Hui Guo; Zhenxing Liu (Aquaculture, 2025)

Self-healing physiological monitoring epidermal sensors of dual conductivity pathway with self-adaptive transformation - Liao Ziming; Zhu Ximing; Zhang Shuquan; Liu Tingting; Song Jiamei; Wang Yuhong; Guo Yanping; Li Xiaohong; Ji Xiaoyuan; Yao Bin (Chemical Engineering Journal, 2025)

Neurotoxicity study of cenobamate-induced zebrafish early developmental stages - Jiahao Liu; Liya Fang; Chao Gong; Jiawei Li; Yuanyuan Liu; Pei Zeng; Yanping Fan; Yao Liu; Jin Guo; Luchuan Wang; Yue Li (Toxicology and Applied Pharmacology, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

Occurrence and ecological risk of disinfection byproducts in urban water body during the pandemic in the Pearl River Delta - Huazhi Wu; Lin Zhang; Pengran Guo; Yanping Zhao; Yumei Song; Xuerong Zhang; Yongqian Lei; Jingwei Xu (Journal of Hazardous Materials, 2025)

Engineered ADSCs and doxycycline encapsulated antibacterial, immunomodulatory and proangiogenic hydrogels for infected burn wound healing - Yanan Gu; Zhen Liang; Yanping Wang; Zhou Yu; Yubo Shi; Jinlong Luo; Xianghao Xu; Ke Fang; Hanli Wang; Baolin Guo; Baoqiang Song; Xin Zhao (Chemical Engineering Journal, 2025)

Fusarium oxysporum causes the root rot disease of Polygonatum cyrtonema in China - Jiuchun An; Lu Luo; Xiaohong Ou; Yanping Gao; Lanping Guo; Chenghong Xiao; Weike Jiang; Tao Zhou; Qing-Song Yuan (Crop Protection, 2024)

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

Unveiling the impact of exposed mineral facets on chromium repartitioning in aging lepidocrocite - Xiaofei Li; Chuling Guo; Xiaohu Jin; Qian Yao; Yanping Bao; Xueding Jiang; Guining Lu; Suresh C. Pillai; Hailong Wang; Zhi Dang (Science of The Total Environment, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Ecologically friendly remediation of groundwater sulfamethoxazole contamination: Biologically synergistic degradation by thermally modified activated carbon-activated peracetic acid in porous media - Si Li; Ruizhe Xu; Luochao Wan; Chaomeng Dai; Jixiang Li; Xueji You; Yanping Duan; Xiaoying Lai; Zhi Li; Jifeng Guo; Yalei Zhang; Jiajun Hu; et al. (Journal of Hazardous Materials, 2024)

Insights into the interactions of plant-associated bacteria and their role in the transfer of antibiotic resistance genes from soil to plant - Yanping Shen; Baiyu Zhang; Ye Yao; Hanbo Wang; Zhilu Chen; Anjing Hao; Ping Guo (Journal of Hazardous Materials, 2024)

Effect of Cd2+ and Cu2+ on Desulfovibrio vulgaris strain ATCC 7757: Insights from sulfur isotope fractionation - Qinglin Zhuang; Chuling Guo; Siyu Zhang; Meihui Ren; Yanping Deng; Chaoping Wang; Han Ye; Zhi Dang (Journal of Environmental Chemical Engineering, 2024)

Characteristics of volatile organic compounds under different operating conditions in a petrochemical industrial zone and their effects on ozone formation - Yanping Yang; Xianhong Meng; Qiang Chen; Qiang Xue; Lina Wang; Jian Sun; Wenkai Guo; Huijie Tao; Lili Yang; Feifei Chen (Environmental Pollution, 2024)

Effects of valley topography on ozone pollution in the Lanzhou valley: A numerical case study - Wenkai Guo; Yanping Yang; Junke Zhang; Keran Han; Yinhua Yang; Qiang Chen; Shixue Li; Yuhuan Zhu (Environmental Pollution, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Experimental investigation on strength characteristics of marine soft clay under monotonic and cyclic loading - Lin Guo; Hao Wu; Yanping He; Hui Li; Yilong Sun (Marine Georesources & Geotechnology, 2024)

Effect of Mn(II) photochemical oxidation on Cd immobilization in hematite - Jiawei Zhang; Chuling Guo; Yuting Zhou; Yanping Deng; Zhi Dang (Journal of Hazardous Materials, 2024)

Driving mechanism of land use and landscape pattern to phytoplankton and zooplankton community and their trophic interactions in river ecosystems - Litao Hao; Yixin Zhang; Yanping Shen; Yibo Liu; Hongjie Gao; Ping Guo (Journal of Environmental Management, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Sulfidation of Cd-Sch during the microbial sulfate reduction: Nanoscale redistribution of Cd - Yanping Deng; Changdong Ke; Meihui Ren; Ziran Xu; Siyu Zhang; Zhi Dang; Chuling Guo (Science of The Total Environment, 2024)

Effects of Na+/H2O2 on nitrogen removal and sludge activity: Performance and mechanism - Lanhe Zhang; Shan Jiang; Yanping Jia; Mingshuang Zhang; Jingbo Guo (Journal of Environmental Chemical Engineering, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Effect of biochar-derived DOM on contrasting redistribution of chromate during Schwertmannite dissolution and recrystallization - Xiaofei Li; Tianfu Li; Paramsothy Jeyakumar; Jiayi Li; Yanping Bao; Xiaohu Jin; Jun Zhang; Chuling Guo; Xueding Jiang; Guining Lu; Zhi Dang; Hailong Wang (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Electrochemistry promotion of Fe(Ⅲ)/Fe(Ⅱ) cycle for continuous activation of PAA for sludge disintegration: Performance and mechanism - Jing Zhang; Yanping Zhang; Ning Lv; Fen Li; Yibing Li; Zhenjie Guo (Environmental Research, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Dominant microbiome iteration and antibiotic resistance genes propagation way dictate the antibiotic resistance genes contamination degree in soil-plant system - Yanping Shen; Cancan Jiang; Baiyu Zhang; Hongjie Gao; Xu Wang; Ping Guo (Journal of Cleaner Production, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Involvement of a rice mutation in storage protein biogenesis in endosperm and its genomic location - Huaidong Tian; Ying Li; Yanping Guo; Yajuan Qu; Xiaoye Zhang; Xiaoxian Zhao; Xinya Chang; Baohua Tian; Guangyuan Wang; Xiangmei Yuan (Planta, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Correction: Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Ecological risk assessment of the typical anti-epidemic drugs in the Pearl River Delta by tracing their source and residual characteristics - Huazhi Wu; Liying Bin; Pengran Guo; Yanping Zhao; Chao Chen; Zhiliang Chen; Bing Tang (Journal of Hazardous Materials, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

Sulfate availability drives the reductive transformation of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Yanping Deng; Siyu Zhang; Meihui Ren; Bingcheng Liu; Jingyi He; Renren Wu; Zhi Dang; Chuling Guo (Science of The Total Environment, 2024)

Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2023)

Transfer of antibiotic resistance genes from soil to wheat: Role of host bacteria, impact on seed-derived bacteria, and affecting factors - Yanping Shen; Yibo Liu; Yutong Du; Xu Wang; Jiunian Guan; Xiaohui Jia; Fukai Xu; Ziwei Song; Hongjie Gao; Baiyu Zhang; Ping Guo (Science of The Total Environment, 2023)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Carcass meat quality, volatile compound profile, and gene expression in Tan sheep under different feeding regimes - Xingang Zhao; Shuxian Zuo; Yanping Guo; Can Zhang; Yuejun Wang; Sijia Peng; Ming Liu; Bing Wang; Hao Zhang; Hailing Luo (Food Bioscience, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

Insight into the plant-associated bacterial interactions: Role for plant arsenic extraction and carbon fixation - Yibo Liu; Baiyu Zhang; Ye Yao; Bo Wang; Yiqi Cao; Yanping Shen; Xiaohui Jia; Fukai Xu; Ziwei Song; Chengpeng Zhao; HongJie Gao; Ping Guo (Science of The Total Environment, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Effects of freeze-thaw dynamics and microplastics on the distribution of antibiotic resistance genes in soil aggregates - Fukai Xu; Jiunian Guan; Yumei Zhou; Ziwei Song; Yanping Shen; Yibo Liu; Xiaohui Jia; Baiyu Zhang; Ping Guo (Chemosphere, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Nanoplastics impacts on Thiobacillus denitrificans: Effects of size and dissolved organic matter - Yuancheng Li; Chuling Guo; Siyu Zhang; Changdong Ke; Yanping Deng; Zhi Dang (Environmental Pollution, 2023)

High expression of HOXC6 predicts a poor prognosis and induces proliferation and inflammation in multiple myeloma cells - Zhihua Li; Yaru Wang; Xiaoxu Hou; Luyao Guo; Yanling Li; Yanping Ma; Yanping Ma (Genes & Genomics, 2023)

A novel high-stability bioelectrochemical sensor based on sol-gel immobilization of lactate dehydrogenase and AuNPs-rGO signal enhancement for serum pyruvate detection - Yanping Zhao; Xu Geng; Xiaoling Zhou; Li Xu; Shuai Li; Zhengqiang Li; Yi Guo; Chen Li (Analytica Chimica Acta, 2023)

Microbial reduction of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Chuling Guo; Siyu Zhang; Yanping Deng; Xiaofei Li; Yuancheng Li; Guining Lu; Fei Ling; Zhi Dang (Science of The Total Environment, 2023)

Characteristics of volatile organic compounds and secondary organic aerosol pollution in different functional areas of petrochemical industrial cities in Northwest China - Yanping Yang; Wenkai Guo; Jian Sun; Qiang Chen; Xianhong Meng; Lina Wang; Huijie Tao; Lili Yang (Science of The Total Environment, 2023)

Catalytic ozonation mechanisms of Norfloxacin using Cu–CuFe2O4 - Lanhe Zhang; Yiran Li; Jingbo Guo; Zhongfeng Kan; Yanping Jia (Environmental Research, 2023)

Luffa rootstock enhances salt tolerance and improves yield and quality of grafted cucumber plants by reducing sodium transport to the shoot - Zhixin Guo; Yanping Qin; Jingli Lv; Xiaojie Wang; Han Dong; Xiaoxing Dong; Tao Zhang; Nanshan Du; Fengzhi Piao (Environmental Pollution, 2023)

Auxin and CmAP1 regulate the reproductive development of axillary buds in Chinese chestnut (Castanea mollissima) - Yunhe Cheng; Lili Cheng; Guanglong Hu; Xiaomeng Guo; Yanping Lan (Plant Cell Reports, 2022)

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Prevalence and risk factors of cardiovascular diseases and psychological distress among female scientists and technicians - Lijun Zhang; Yanping Bao; Guo Li; Shuhui Tao; Meiyan Liu (Journal of Zhejiang University-SCIENCE B, 2022)

Clean technology investment considering synergistic effects: a case from the steel sintering process - Jianxin Guo; Xianchun Tan; Xiaoyan Meng; Yanping Li (Environment, Development and Sustainability, 2022)

Poor evidence for host-dependent regular RNA editing in the transcriptome of SARS-CoV-2 - Jinbao Zong; Yanping Zhang; Fenfen Guo; Changyuan Wang; Hong Li; Gaoyang Lin; Wenqing Jiang; Xiaoping Song; Xiufang Zhang; Feng Huang; Min Qi; Xin Zheng (Journal of Applied Genetics, 2022)

Study on the Individual Coloring Mechanism of Iridescent Cells in the Mantle of the Boring Giant Clam, Tridacna crocea - Yunqing Li; Yinyin Zhou; Jinkuan Wei; Gongpengyang Shi; Qingliang Liao; Shuming Guo; Zihua Zhou; Jun Li; Yanping Qin; Haitao Ma; Ziniu Yu; Yuehuan Zhang (Frontiers in Marine Science, 2022)
Giant clams are marine bivalves that inhabit Indo-Pacific coral reefs. The boring giant clam, Tridacna crocea , exhibits bright and conspicuous mantle coloration based on the specialized cells (iridocytes) that generate structural colors. In order to illustrate the coloring mechanism of individual iridocytes, the reflection spectra curve of iridocytes was obtained by a micro-hyperspectral imager. TEM images were obtained to show the inner nanostructures of iridocytes. FDTD simulation was conducted to analyze the relationship between the color of iridocytes and the unique lamellar structure. We found that the laminae in the regular arrangement within cells govern the coloration of individual iridocytes. With the gradual increase of lamellar thickness and spacing, the color of the structure varies from bright violet to orange-red, forming a full visible spectrum. This study provides a new understanding of the various colors produced by individual iridocytes.

Dopaminergic Neurons in the Ventral Tegmental–Prelimbic Pathway Promote the Emergence of Rats from Sevoflurane Anesthesia - Yanping Song; Ruitong Chu; Fuyang Cao; Yanfeng Wang; Yanhong Liu; Jiangbei Cao; Yongxin Guo; Weidong Mi; Li Tong (Neuroscience Bulletin, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Localization and regulatory function of Yin Yang 1 (YY1) in chicken testis - Ligen Chen; Lingyun Qiao; Yan Guo; Ying Huang; Wei Luo; Yanping Feng (Molecular Genetics and Genomics, 2022)

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

SETD4 in the Proliferation, Migration, Angiogenesis, Myogenic Differentiation and Genomic Methylation of Bone Marrow Mesenchymal Stem Cells - Xiaomin Liao; Caixia Wu; Zhongming Shao; Shuya Zhang; Yuan Zou; Keke Wang; Yanping Ha; Jingci Xing; Axiu Zheng; Zhihua Shen; Shaojiang Zheng; Junli Guo; et al. (Stem Cell Reviews and Reports, 2021)

Overexpression of KcNHX1 gene confers tolerance to multiple abiotic stresses in Arabidopsis thaliana - Yanqin Wang; Yuan Guo; Fen Li; Yanping Liu; Shuangxia Jin (Journal of Plant Research, 2021)

Sulfate-reducing bacterial community shifts in response to acid mine drainage in the sediment of the Hengshi watershed, South China - Yanping Bao; Xiaohu Jin; Chuling Guo; Guining Lu; Zhi Dang (Environmental Science and Pollution Research, 2021)

Effects of EDTA on adsorption of Cd(II) and Pb(II) by soil minerals in low-permeability layers: batch experiments and microscopic characterization - Xueji You; Shuguang Liu; Chaomeng Dai; Guihui Zhong; Yanping Duan; Yiping Guo; Aleksei Nikolavich Makhinov; José Tavares Araruna Júnior; Yaojen Tu; Kah Hon Leong (Environmental Science and Pollution Research, 2020)

New Insights on ‘GALA’ Apple Fruit Development: Sugar and Acid Accumulation: A Transcriptomic Approach - Hongxia Tao; Hanqing Sun; Yufei Wang; Xuena Song; Yanping Guo (Journal of Plant Growth Regulation, 2020)

Blueberry VcLon1 protease increases iron use efficiency by alleviating chloroplast oxidative stress - Jingya Zhong; Jiajia Gu; Yanping Guo; Shibei You; Fanglei Liao; Wenrong Chen; Weidong Guo (Plant and Soil, 2019)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line - Gang Su; Wenke Yang; Wenbo Meng; Qionghui Wu; Yanping Luo; Xingming Ma; Shen Zhao; Xiaodong Xie; Guang-Qin Guo (Natural Product Research, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Partial shade optimizes photosynthesis and growth in bayberry (Myrica rubra) trees - Guanghui Zeng; Yanping Guo; Jianxu Xu; Meijun Hu; Jie Zheng; Zhenwang Wu (Horticulture, Environment, and Biotechnology, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

Cycloartane-type triterpenoids from Astragalus hoantchy French. - Kai Guo; Xiaofeng He; Dengxue Lu; Yanping Zhang; Xiuzhuang Li; Zhiqiang Yan; Bo Qin (Natural Product Research, 2017)

Changes in endogenous hormones and H2O2 burst during shoot organogenesis in TDZ-treated Saussurea involucrate explants - Bin Guo; Wei He; Yan Zhao; Yandi Wu; Yanping Fu; Juan Guo; Yahui Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Characterization of eleven microsatellite markers for the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) - Shengli Jing; Baoxiao Zheng; Li Qiao; Kun Zhang; Gaoyang Chen; Shunqin Guo; Xiaoyan Huang; Yanping Gao; Lili Zhang; Hongyu Yuan (Applied Entomology and Zoology, 2016)

Down-Regulation of ClC-3 Expression Reduces Epidermal Stem Cell Migration by Inhibiting Volume-Activated Chloride Currents - Rui Guo; Fuqiang Pan; Yanping Tian; Hongli Li; Shirong Li; Chuan Cao (The Journal of Membrane Biology, 2016)

Human cytomegalovirus-encoded miR-US4-1 promotes cell apoptosis and benefits discharge of infectious virus particles by targeting QARS - Yaozhong Shao; Ying Qi; Yujing Huang; Zhongyang Liu; Yanping Ma; Xin Guo; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2016)

Human cytomegalovirus miR-UL36-5p inhibits apoptosis via downregulation of adenine nucleotide translocator 3 in cultured cells - Xin Guo; Yujing Huang; Ying Qi; Zhongyang Liu; Yanping Ma; Yaozhong Shao; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2015)

Analysis of Bacterial Diversity During Acetic Acid Fermentation of Tianjin Duliu Aged Vinegar by 454 Pyrosequencing - Qian Peng; Yanping Yang; Yanyun Guo; Ye Han (Current Microbiology, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

Comparative Genomic Analysis of Two-Component Signal Transduction Systems in Probiotic Lactobacillus casei - Shuijing Yu; Yanping Peng; Wanyi Chen; Yangwu Deng; Yanhua Guo (Indian Journal of Microbiology, 2014)

The structural characteristics of precipitation in Asian-Pacific’s three monsoon regions measured by tropical rainfall measurement mission - Jiangnan Li; Yanping Zheng; Fangzhou Li; Feiyun Guo; Weibiao Li (Acta Oceanologica Sinica, 2014)

Lin-28 reactivation is required for let-7 repression and proliferation in human small cell lung cancer cells - Lin Pan; Zhaohui Gong; Zhiwei Zhong; Zhuo Dong; Qiong Liu; Yanping Le; Junming Guo (Molecular and Cellular Biochemistry, 2011)

ABCC10, ABCC11, and ABCC12 - Gary D. Kruh; Yanping Guo; Elizabeth Hopper-Borge; Martin G. Belinsky; Zhe-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2007)

Genomic comparison of Yersinia pestis and Yersinia pseudotuberculosis by combination of suppression subtractive hybridization and DNA microarray - Xiaoyi Wang; Dongsheng Zhou; Long Qin; Erhei Dai; Jianguo Zhang; Yanping Han; Zhaobiao Guo; Yajun Song; Zongmin Du; Jin Wang; Jun Wang; Ruifu Yang (Archives of Microbiology, 2006)